A review of 2.45 GHz microstrip patch antennas for wireless applications - Rana, Md. Sohel; Rocky, Tanvir Rahman; Islam, Md. Arif; Mamun, Al; Joy, Sanjay Kumar; Mondal, Saikat; Ahmed, Md. Toukir; Islam, Md. Hasibul; Pal, Sourav; Chowdhury, Imran; Faruq, Omar (Institute of Advanced Engineering and Science, 2024)
Recently, microstrip patch antennas have become popular. Due to their ubiquity, these antennas have more uses every day. In this research paper, a 2.45 GHz microstrip patch antenna has been reviewed and analyzed. Different substrate materials have been used to make these antennas, and their thickness is different. Various antennas are designed based on the application, such as rectangular, square, triangle, ring, donut, and dipole. Other types of software were used to design the antenna, including CST, HFSS, MATLAB, ADS, and FEKO. Microstrip patch antenna design is a relatively new field of study for wireless applications. Several devices are linked to send or receive radio waves using a single antenna. Antennas designed for 2.45 GHz are used in various wireless communication systems, including television broadcasts, microwave ovens, mobile phones, wireless local area network (WLAN), Bluetooth, global positioning system (GPS), and two-way radios. This article looks at the geometric structures of antennas, including their many parameters and materials and the many different shapes they can take. In addition, the substrate materials, the loss tangent, the thickness, the return loss, the bandwidth, the voltage standing wave ratio (VSWR), the gain, and the directivity of previous articles will also be discussed.